Microstructure Changes and Improvement in the Mechanical Properties of As-Cast AlSi7MgCu0.5 Alloy Induced by the Heat Treatment and ECAP Technique at Room Temperature - Miloš Matvija; Martin Fujda; Ondrej Milkovič; Marek Vojtko; Róbert Kočiško; Miroslav Glogovský (Advances in Materials Science and Engineering)
The changes in the microstructure and improvement in the mechanical properties of as-cast AlSi7MgCu0.5 alloy induced by the heat treatment and technique of equal channel angular pressing (ECAP) were investigated. The heat treatment of as-cast alloy performed before the ECAP technique was required to increase the plasticity of the alloy. Therefore, the samples of analysed alloys were solution annealed at optimized temperature of 823 K for 4 hours to dissolve the particles of intermetallic π(Al8FeMg3Si6) phase and to spheroidize the Si particles. Subsequently, water quenching and artificial ageing at optimized temperature of 573 K for 5 hours was used to obtain an overaged alloy state. The microstructure of alloy was consisted of α(Al) solid solution, eutectic Si particles, and intermetallic β(Mg2Si), Q-Al4Mg5Si4Cu, α-Al12(Fe,Mn)3Si, and/or α-Al15(Fe,Mn)3Si2 phase particles. The crystal structure of present phases was confirmed by hard X-ray diffraction at Deutsches Elektronen-Synchrotron (DESY) in Hamburg and by the selected area electron diffraction (SAED) performed inside the transmission electron microscope (TEM). The heat-treated alloy was processed by ECAP at room temperature following route A. Repetitive ECAP of alloy homogenized the heterogeneous as-cast microstructure and formed the ultrafine subgrain microstructure with elongated subgrains of 0.2 µm in width and 0.65 µm in length and the high dislocation density. Microstructural changes in alloy induced by both heat treatment and ECAP led to the high strain hardening of the alloy that appeared in an improvement in strength, ductility, and microhardness of alloy in comparison with as-cast alloy state.